ENGLISH FOR AGRONOMISTS - Symaka, Anna; Melnychuk, Natalia (My University, 2024)
This manual is intended for students, teachers, researchers, and practitioners who are interested in the field of agronomy, which is the science and practice of crop production and soil management. Agronomy covers a wide range of topics, from botany and plant physiology to agroecology and agricultural economics. This manual aims to provide an overview of the main aspects of agronomy, as well as practical guidance on how to apply agronomic principles and practices in different contexts.
Keywords: Agronomy, Botany, Soil, Horticulture, Agriculture